Carbon Footprint Evaluation and Environmental Sustainability Improvement through Capacity Optimization - Orovwode, Hope Evwieroghene; Matthew, Simeon; Amuta, Elizabeth; Agbetuyi, Felix Ayoade; Odun-Ayo, Isaac (International Journal of Energy Economics and Policy, 2021)
The burning of fossil fuel for power generation emits Greenhouse gases into the environment. Greenhouse Gases (GHGs) emission is the principal cause of global warming. In order to regulate the emissions of these gases, the emissions need to be assessed and quantified. Carbon footprint is the evaluation of human activities that lead to GHGs emissions. The Covenant University Electricity Network during periods when utility supply fail runs on diesel powered generators located at different centers within the campus. These generators emit carbon-based compounds into the environment. Assessing the quantity of carbon dioxide which is the principal GHGs emitted per year gives 33.14-tonnes. Analysis of the load profiles in the centers showed that all the eight generators are not supposed to be running simultaneously as it is now. This study developed a new network model where all the generators were integrated into a DC microgrid that ensured resource sharing. The model was simulated using energy management and optimization techniques resulting in reduced micro-generators engagement, Green House Gases emission and fuel consumption. Consequently, carbon dioxide emitted per year dropped to 18.44-tonnes from 33.14-tonnes. The developed model improved the carbon footprint of the campus by as much as 44.3%. Keywords: Greenhouse gases, Climate change, Carbon footprint, optimization, energy management JEL Classifications: Q5, Q430, L94 DOI: https://doi.org/10.32479/ijeep.10209